The effect of instructional support on learning gains from two simulated laboratory experiments on the relationship between two variables - Sönmez, Nuray. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The present study attempts to understand the effect of additional instructional support in recognizing and recalling the relationships between two variables in two simulated laboratory experiments which include multiple representations. It was carried out with the seventh graders in a public primary school in Istanbul. Pretest-posttest group design was used in this study. 44 seventh grade students were assigned randomly into two groups each consists of 22 students but trying to match the groups according to their sixth class science and math grade means and gender. Both groups were administered a pretest called “Test on Relationships between two Variables” (TR-b2V pretest) and both made the same two simulated experiments on the computer laboratory. However, the supported group (Group S) completed a worksheet given as an additional instructional support during the simulated lab experiments whereas non-supported group (Group NS) worked only with guides included in the simulation environment. Both groups received two post measures. Firstly, Recall of Representation Test (RRT) was administered to assess the degree to which students could recall the representations in the simulation environment. Secondly TR-b2V was administered as a posttest four days after the treatment. Findings indicated a significant difference between pretest and posttest results for all participants. However, no significant difference was found between the Group S and Group NS in terms of learning gains which was calculated by differences of pretest and posttest scores. Worksheets did not result in significant improvements in the performance of Group S according to Group NS. Similarly, the Group S performed not significantly higher than the Group NS in terms of RRT scores although RRT mean of Group S was higher than RRT mean of Group NS. Therefore, the positive effect of the additional instructional support in two simulated lab experiments was inconclusive in terms of learning gains and recalling performance of the seventh graders.
Keywords: Computer-assisted instruction.; Audio-visual education.